Rachel Rourke's 8th Birthday Celebration at Rollertown - Watkins, Howard::::::::: (1989)
Group photo: 1st row: ?, Rachel Roelke and ?r, 2nd row: Robin Watkins, ?, ?, Veronica Velasquez; 3rd row: ?, Mary Roelke, Robert Roelke and ?